Abnormal Visual Evoked Responses to Emotional Cues Correspond to Diagnosis and Disease Severity in Fibromyalgia - Goldway, Noam; Petro, Nathan M.; Ablin, Jacob; Keil, Andreas; Ben Simon, Eti; Zamir, Yoav; Weizman, Libat; Greental, Ayam; Hendler, Talma; Sharon, Haggai (Frontiers in Behavioral Neuroscience, 2022)
Background Chronic pain disorders are often associated with cognitive-emotional dysregulation. However, the relations between such dysregulation, underlying brain processes, and clinical symptom constellations, remain unclear. Here, we aimed to characterize the abnormalities in cognitive-emotional neural processing involved in chronic pain and their relation to disease diagnosis and severity, by examining attentional-emotional disturbances in patients with fibromyalgia syndrome (FMS). Methods Fifty-eight participants, 39 FMS patients (35F), and 19 healthy control subjects (16F) participated in this study and performed an EEG-based paradigm assessing attention allocation by extracting steady-state visually evoked potentials (ssVEP) in response to affective distractors presented during a cognitive task. Patients were also evaluated for pain severity, sleep quality, depression, and anxiety. Results EEG ssVEP measurement indicated that, compared to healthy controls, FMS patients displayed impaired affective discrimination, and sustained attention to negative distractors. Moreover, patients displayed decreased task-related fronto-occipital EEG connectivity. Lack of adaptive attentional discrimination, measured via EEG, was predictive of pain severity, while impairments in fronto-occipital connectivity were predictive of impaired sleep. Conclusions FMS patients display maladaptive affective attention modulation, with abnormal task-related cortical activity, which differentially predicts disease-relevant symptoms. These findings are consistent with current notions ascribing a critical role for cognitive-emotional dysregulation in the pathophysiology and clinical symptomatology of chronic pain.